2017
DOI: 10.1111/mec.14124
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of the hyperinvasive vine, Mikania micrantha (Asteraceae), via admixture and founder events inferred from population transcriptomics

Abstract: Biological invasions that involve well-documented rapid adaptations to new environments provide unequalled opportunities for testing evolutionary hypotheses. Mikania micrantha Kunth (Asteraceae), a perennial herbaceous vine native to tropical Central and South America, successfully invaded tropical Asia in the early 20th century. It is regarded as one of the most aggressive weeds in the world. To elucidate the molecular and evolutionary processes underlying this invasion, we extensively sampled this weed throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 74 publications
3
23
0
Order By: Relevance
“…Interbreeding multiple sources are also frequent (Facon et al, 2005;Keller & Taylor, 2010;Nelson, Wallberg, Simões, Lawson, & Webster, 2017;Rius & Darling, 2014;Yang et al, 2017), and even the "hybrid swarm" we observe in S. alterniflora is not unique and has been reported for several invasive species (Boyer, Muhlfeld, & Allendorf, 2008;Gammon, Grimsby, Tsirelson, & Kesseli, 2007;Glotzbecker, Walters, & Blum, 2016;Roy et al, 2015). Our study thus suggests that it is crucial to consider the long-term impact of admixture while evaluating the risk of multiple introductions and predicting the velocity of geographic scale expansion.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Interbreeding multiple sources are also frequent (Facon et al, 2005;Keller & Taylor, 2010;Nelson, Wallberg, Simões, Lawson, & Webster, 2017;Rius & Darling, 2014;Yang et al, 2017), and even the "hybrid swarm" we observe in S. alterniflora is not unique and has been reported for several invasive species (Boyer, Muhlfeld, & Allendorf, 2008;Gammon, Grimsby, Tsirelson, & Kesseli, 2007;Glotzbecker, Walters, & Blum, 2016;Roy et al, 2015). Our study thus suggests that it is crucial to consider the long-term impact of admixture while evaluating the risk of multiple introductions and predicting the velocity of geographic scale expansion.…”
Section: Discussionsupporting
confidence: 65%
“…However, the conclusions of rapid evolution are often blurred by the stochasticity of introduction and dispersal, as the exact sources of introduction are often inaccessible (Colautti & Lau, 2015;Keller & Taylor, 2008). In contrast, many population genetic surveys throughout the native and invasive range have located the sources and revealed patterns of genetic admixtures (Krehenwinkel & Tautz, 2013;Lombaert et al, 2011;Roy, Lucek, Walter, & Seehausen, 2015;Yang et al, 2017), but the evolutionary consequences are not investigated. Moreover, to determine the drivers of evolution and the selective agents, it is crucial to incorporate classic approaches in phenotypic evolution, such as reciprocal transplant experiments (Colautti & Lau, 2015).…”
mentioning
confidence: 99%
“…Similarly, two clusters in Western and Eastern Europe have been identified as the sources of the American weed Centaurea solstitialis (Barker, Andonian, Swope, Luster, & Dlugosch, ). Thirdly, a wide scale study of the invasive weed Mikania micrantha in South‐East Asia demonstrated the existence of two distinct genetics clusters that resulted from separate introductions originating from the native American range (Yang et al, ). Studies on invasive trees are less numerous, but they have generally concluded that multiple introductions occurred (Besnard et al, ; Merceron et al, ; Pairon et al, ; Thompson et al, ) without being able to clearly identify the population sources.…”
Section: Discussionmentioning
confidence: 99%
“…Uller and Leimu (2011) demonstrated that genetic variation between native and invasive ranges was influenced by taxonomy: Invasive animals often suffered a loss of genetic diversity between the ranges, whereas invasive plants often exhibited higher genetic diversity in the invasive range (Uller & Leimu, 2011). According to these authors, one factor contributing to this pattern is that invasive animal populations are often founded by single introduction events, whereas multiple introductions associated with admixture are more common for plants (Uller & Leimu, 2011 (Yang et al, 2017). Studies on invasive trees are less numerous, but they have generally concluded that multiple introductions occurred (Besnard et al, 2014;Merceron et al, 2017;Pairon et al, 2010;Thompson et al, 2015) without being able to clearly identify the population sources.…”
Section: Evidencing the Bottleneck Depends On The Set Of Genotyped mentioning
confidence: 99%
“…These ecological transcriptome studies allow a connection between genotypic variation into complex trait phenotypes as modulated by the prism of the natural environment. Such studies have now become increasingly popular, and have been undertaken in A. thaliana (Richards et al ., ; Tyagi et al ., ) and crops (Plessis et al ., ; Russell et al ., ; Zhao et al ., ), tree species (Philippe et al ., ; Verta et al ., ), lesser known plant species (Jia et al ., ; Yang et al ., ), and energy crops like switchgrass (Palmer et al ., ) and Miscanthus (Song et al ., ; Yan et al ., ; Xing et al ., ).…”
Section: From Lab To the Field: Plant Genomics And Systems Biology Imentioning
confidence: 99%